My first atlas of the world - Sharma, Martha B.; Powers-Kaminski, Skye; Klein, Tovah P. (Washington, D.C. : National Geographic, 2023)
Presents an overview of the countries of the world, explaining how to look at a map, where people live on the Earth, and major countries and regions.
Glossary.
Ages 3-6.
Keywords: Geography; Maps